CODE MIXING USED BY STUDENTS OF FRENCH STUDY PROGRAM STATE UNIVERSITY OF MEDAN - Windi Sahputra Barus; Mhd. Pujiono; Hesti Fibriasari (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2019)
The communication process involving a code mixing is an alternative to avoid misunderstandings in a bilingual community, a community having the phenomenon of speaking and understanding two or more languages, referring either to individuals or the entire society. This study aims to analyze the forms of code mixing using qualitative method. The data were obtained from recording of conversational discourse. The data collection strategy used the referral method, supported by basic techniques, namely tapping and advanced techniques, the skillful in-flight listening technique (SBLC). The results show that there are code mixing with the insertion of morphological elements in forms of nouns, numerals, verbs (infinitive and conjugation), adverbs (question and time), and adjectives;   the insertion of phrase in terms of noun phrases (objects and numerals), verb phrases, and adverb phrases); the insertion of clause in the forms of noun clauses, numeral clauses, verb clauses, and adverb clauses; and the insertion of idiomatic forms.  Code mixing of students of French language is also found in English language.